Location Quotient Analysis of Agricultural Sector and Subsector in East Java 2010-2017 (A Reference for Law and Policy on Economics, Nutrition and Public Health) - Erlambang Budi Darmanto1, Yunita Satya Pratiwi2, Heru Santoso Wahito Nugroho3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Indonesia is known as an agrarian country, should rely on the agricultural sector as an economic source as well as supporting development. In addition to the economic aspects, the progress of agriculture is also very important for the provision of nutrients for the maintenance and improvement of public health. This study uses the Location Quotient method to obtain a base subsector in the agricultural sector, so that the results can be used as material for consideration of export specialties. This study uses East Java GRDP data and as a comparison using Indonesia’s GRDP in 2010-2016. The results in this study indicate that the food crop and livestock sub-sector has an advantage compared to other sub-sectors and becomes a subsector of the base, so that these two sub-sectors can be used as export products for East Java.